KLF13 is a genetic modifier of the Holt-Oram syndrome gene TBX5. (9th January 2017) - Darwich, Rami; Li, Wenjuan; Yamak, Abir; Komati, Hiba; Andelfinger, Gregor; Sun, Kun; Nemer, Mona
Abstract: TBX5, a member of the T-box family of transcription factors, is a dosage sensitive regulator of heart development. Mutations in TBX5 are responsible for Holt-Oram Syndrome, an autosomal dominant disease with variable and partially penetrant cardiac defects suggestive of the existence of genetic and environmental modifiers. KLF13, a member of the Krüppel-like family of zinc finger proteins is co-expressed with TBX5 in several cardiac cells including atrial cardiomyocytes and cells of the interatrial septum. We report that KLF13 interacts physically and functionally with TBX5 to synergistically activate transcription of cardiac genes. We show that TBX5 contacts KLF13 via its T-domain and find that several disease-causing mutations therein have decreased KLF13 interaction. Whereas Klf13 heterozygote mice have no detectable cardiac defects, loss of a Klf13 allele in Tbx5 heterozygote mice significantly increases the penetrance of TBX5-dependent cardiac abnormalities including atrial, atrial-ventricular and ventricular septal defects. The results reveal for the first time combinatorial interaction between a T-box protein and a KLF family member and its importance for heart and possibly other organ development. The data also suggest that, in human, KLF13 may be a genetic modifier of the Holt-Oram Syndrome gene TBX5.